THE EFFECT OF INTEREST, SELF-EFFICACY, AND INTRINSIC MOTIVATION ON THE DECISION TO CHOOSE ACROSS ECONOMIC INTERESTS AT SMAN 1 GUNUNG TALANG - Nuraris Santi Dewi; Friyatmi Friyatmi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
This study aims to find out how interest, self-efficacy, and intrinsic motivation influence students' decisions to choose across economic interests at SMAN 1 Gunung Talang. This research method is a quantitative descriptive. The sampling technique used proportional random sampling. Data collection with a questionnaire. Data analysis with path analysis. The results of the study show that interest has a significant and positive effect on intrinsic motivation with a path coefficient of 0.451, self-efficacy has a significant and positive effect on students' intrinsic motivation with a path coefficient of 0.249, interest has a significant and positive effect on the decision to choose students with a path coefficient of 0.226, self-efficacy has a significant and positive effect on the decision to choose students with a path coefficient of 0.184, intrinsic motivation has a significant and positive effect on the decision to choose students with a path coefficient of 0.378, interest has a significant effect on the decision to choose through intrinsic motivation as an intervening variable, and self-efficacy has a significant and positive effect on cross-choice decisions on economic interest in SMAN 1 Gunung Talang through intrinsic motivation as an intervening variable.